2021
DOI: 10.29303/jppipa.v7ispecialissue.863
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Growth of Sweet Corn (Zea mays L. Saccharata) Due to Difference Doses of Horse Manure Compost and NPK Fertilizer

Abstract: Sweet corn has a sturdy and strong stem growth and is very suitable for cultivation in tropical climates. Research on the effect of horse manure compost combined with NPK fertilizer on the growth of sweet corn has been done with the aim of obtaining information: (1) the effect of different doses of horse manure compost on the growth of sweet corn, (2) the effect of different doses of NPK fertilizer on the growth of sweet corn, (3) The interaction effect of horse manure compost and NPK fertilizer on sweet corn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The application of NPK fertilizer had a significant effect on increasing the leaf width of sweet corn. The dose of 6 grams of NPK fertilizer for one plant gave better results than other treatments [18]. The application of NPK fertilizer had a significant effect on increasing the leaf width and height of green eggplant plants [19].…”
Section: Spinach Leaf Widthmentioning
confidence: 95%
“…The application of NPK fertilizer had a significant effect on increasing the leaf width of sweet corn. The dose of 6 grams of NPK fertilizer for one plant gave better results than other treatments [18]. The application of NPK fertilizer had a significant effect on increasing the leaf width and height of green eggplant plants [19].…”
Section: Spinach Leaf Widthmentioning
confidence: 95%
“…Data on Zea mays plants indicated that the treatment of organic fertilizer from horse manure of 12 tons/ha, 18 tons/ha and 24 tons/ha, respectively, combined with NPK 40 kg/ha, 80 kg/ha and 120 kg/ha, did not have an impact on growth on leaf length, height, number of leaves, stem diameter on day 15, 30 and 45. Will is still single, having a significant impact on growth (Raksun et al, 2021).…”
Section: Figure 7 Average Total Stomatamentioning
confidence: 99%